If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(m-3)+m=7m+43
We move all terms to the left:
9(m-3)+m-(7m+43)=0
We add all the numbers together, and all the variables
m+9(m-3)-(7m+43)=0
We multiply parentheses
m+9m-(7m+43)-27=0
We get rid of parentheses
m+9m-7m-43-27=0
We add all the numbers together, and all the variables
3m-70=0
We move all terms containing m to the left, all other terms to the right
3m=70
m=70/3
m=23+1/3
| 180=2(b-30)+b | | 10-5z=7z+22 | | 2(w-1)=-10(w-3) | | 4x-(2x-4)=2x+4 | | z/4+3=4-z/4 | | 5(2d+3)=-3(-3d-4) | | 2(3x-5)=2(3x-4) | | -22+3x/3x+7=2 | | 1*n+10=17 | | |15x-7|-4=4 | | (3x+2)^2=28 | | 2(4w-1)=-10(w-3)=4 | | 6t+4=3t+2 | | 6x+2=7x+4 | | (x-1)²=16 | | 25x-8=(5)(9)-8 | | x=150000+.0975x | | 13x-12x+1=7 | | 4y-5y=2y-9 | | Y/3=w | | x/2+x/7=7/2 | | 2x^2+22=54 | | 0.2(x+2)=0.5(x+2)-0.2x-0.4 | | -9w+12w=-15 | | (x-1)^2=16 | | 5(-2x+5)+x-5=-43 | | X²+9x-1620=0 | | t-9-3.2=2 | | 43=y+18 | | 2m2+5m+16=8 | | 2z-z-1=11 | | .25x-5=20 |